2015
DOI: 10.1080/1062936x.2014.984628
|View full text |Cite
|
Sign up to set email alerts
|

Prioritization of active antimalarials using structural interaction profile ofPlasmodium falciparumenoyl-acyl carrier protein reductase (PfENR)-triclosan derivatives

Abstract: An empirical relationship between the experimental inhibitory activities of triclosan derivatives and its computationally predicted Plasmodium falciparum enoyl-acyl carrier protein (ACP) reductase (PfENR) dock poses was developed to model activities of known antimalarials. A statistical model was developed using 57 triclosan derivatives with significant measures (r = 0.849, q(2) = 0.619, s = 0.481) and applied on structurally related and structurally diverse external datasets. A substructure-based search on Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…It may be that further engineering of triclosan by synthetic chemistry is necessary to improve delivery and half-life, but with regard to affinity triclosan is a viable non-toxic lead with a mechanism based on hitherto undiscovered selectivity. A number of triclosan analogs have already been synthesized 16 , 21 , demonstrating the ample opportunity for its improvement for use as an antimalarial.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It may be that further engineering of triclosan by synthetic chemistry is necessary to improve delivery and half-life, but with regard to affinity triclosan is a viable non-toxic lead with a mechanism based on hitherto undiscovered selectivity. A number of triclosan analogs have already been synthesized 16 , 21 , demonstrating the ample opportunity for its improvement for use as an antimalarial.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, phenotypical, biochemical, structural evidence, and in silico simulations demonstrated that triclosan is a strong inhibitor of the P . falciparum enoyl reductase ( Pf ENR) 13 , 20 , 21 . However Yu et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past, Kumar et al have identified a class of rhodanine compounds as antimalarials using a docking and lead optimization approach. Consistent progress has been made in docking and inverse‐docking studies in discovering more potent Pf ENR inhibitors . Recently, a multi‐complex‐based pharmacophore modeling approach was used for the identification of structurally diverse ENR inhibitors .…”
Section: Introductionmentioning
confidence: 99%
“…Consistent progress has been made in docking and inverse-docking studies in discovering more potent PfENR inhibitors. 13 Recently, a multi-complex-based pharmacophore modeling approach was used for the identification of structurally diverse ENR inhibitors. 14 Although many studies have reported on the structure-based drug design, very few have focused on the exploration of the dynamic behavior of the ENR protein.…”
mentioning
confidence: 99%